1970
DOI: 10.2307/3479702
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Management of the Public Lands

Abstract: ENviR. REP.-CAsEs] (preliminary injunction barring issuance of federal permit for haul road needed for trans-Alaska pipeline system).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Logging reproduces some of the effects of the fire cycle by clearing away parts of the mature forest. In 1971 Heyman and Twiss [16] observed that "Timber harvest can yield improved habitat for deer and other wildlife," Nevertheless, Weber and Chen [17] note that "Starting in the late 1980s and early 1990s, Federal forest management policy in the Pacific Northwest began to emphasize habitat protection and reduced the timber harvest on Federal lands." A 2015 press report from Oregon [18] observes "some leading scientists support regeneration harvests to create more very young forests favored by deer and elk, conservation groups have opposed them."…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Logging reproduces some of the effects of the fire cycle by clearing away parts of the mature forest. In 1971 Heyman and Twiss [16] observed that "Timber harvest can yield improved habitat for deer and other wildlife," Nevertheless, Weber and Chen [17] note that "Starting in the late 1980s and early 1990s, Federal forest management policy in the Pacific Northwest began to emphasize habitat protection and reduced the timber harvest on Federal lands." A 2015 press report from Oregon [18] observes "some leading scientists support regeneration harvests to create more very young forests favored by deer and elk, conservation groups have opposed them."…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%